2020
DOI: 10.1248/bpb.b20-00325
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Inhibits Resistance to Imatinib by Downregulation of Bcr-Abl and STAT5 and Allosteric Inhibition in Chronic Myeloid Leukemia Cells

Abstract: Imatinib-resistance is a significant concern for Bcr-Abl-positive chronic myelogenous leukemia (CML) treatment. Emodin, the predominant compound of traditional medicine rhubarb, was reported to inhibit the multidrug resistance by downregulating P-glycoprotein of K562/ADM cells with overexpression of P-glycoprotein in our previous studies. In the present study, we found that emodin can be a potential inhibitor for the imatinib-resistance in K562/G01 cells which are the imatinib-resistant subcellular line of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…By inhibiting the BCR-ABL/STAT5 signaling cascade and downstream components involved in apoptosis, Emodin significantly reduced imatinib stimulated apoptosis. Furthermore, emodin had a far stronger affinity for the myristoyl-binding pocket of ABL1 than for the ATP-binding region, indicating that it could augment the efficacy of imatinib [77]. As a result, emodin could become a viable chemotherapeutic drug in the treatment of CML in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By inhibiting the BCR-ABL/STAT5 signaling cascade and downstream components involved in apoptosis, Emodin significantly reduced imatinib stimulated apoptosis. Furthermore, emodin had a far stronger affinity for the myristoyl-binding pocket of ABL1 than for the ATP-binding region, indicating that it could augment the efficacy of imatinib [77]. As a result, emodin could become a viable chemotherapeutic drug in the treatment of CML in the future.…”
Section: Discussionmentioning
confidence: 99%
“…STAT5 has lately emerged as a promising therapeutic target for overcoming BCR-ABL1 kinase antagonist resistance, such as in CML cells with the T315I mutated BCR-ABL[75]. The cotreatment of kinase inhibitor imatinib and Emodin attenuated STAT5 phosphorylation in a concentration-dependent fashion[77].Emodin might actively decrease resistance to imatinib by the K562/G01 cell line via downregulating BCR-ABL1 expression and STAT5 phosphorylation. Emodin is known to have augmented the antagonizing actions of imatinib on the STAT5 signaling and mitogenic BCR-ABL1 pathway in the K562/G01 cells [77].…”
mentioning
confidence: 99%
“…In addition, emodin combined with cytarabine (ARA-C) can significantly inhibit the growth of HL-60/ADR cells in vivo and in vitro through dual targeting of the Akt and ERK pathways 190 . A recent study reported that emodin can enhance the sensitivity of K562/G01 cells to imatinib via inhibition of phosphorylation of Bcr-Abl and STAT5 and phosphorylation of Src 191 (Figure 7 ).…”
Section: Anticancer Effects Of Emodinmentioning
confidence: 97%
“…Endonucleases are the enzymes involved in DNA repair by excision of incorrect nucleotides (ERCC1), whereas the combination of emodin with capecitabine induces cytotoxicity by inhibiting the expression of two proteins Rad51 and ERCC1 [74][75][76]. Moreover, emodin reduces resistance of chronic myeloid leukemia cells to imatinib [77].…”
Section: Effects Of Emodin On the Activity Of Drugsmentioning
confidence: 99%